UTAR heats up as inti falters - The Sun , Kelvin Goh Wong (2010)
The team from Tunku Abdul rahman Universiti (UTAR) showed all shades of ferocity as they took the International Islamic Universiti Malaysia (IIUM) apart, 89-46, making up for their previous lackluster performance against Multimedia Universiti (MMU) in the Universiti College Basketball League (UCBL).